Patients with lymphatic malformations who receive the immunostimulant OK‐432 experience excellent long‐term outcomes. (14th July 2015) - Ghaffarpour, N; Petrini, B; Svensson, LA; Boman, K; Wester, T; Claesson, G
Abstract Aim Sclerotherapy is the primary treatment for lymphatic malformations. The aim of this study was to evaluate the long‐term outcome in patients with lymphatic malformations treated with the immunostimulant OK‐432 as a sclerosant. Methods Between 1998 and 2013, we enrolled 131 of 138 eligible patients treated with OK‐432 for lymphatic malformations in a retrospective study. The malformations were categorised according to the International Society for the Study of Vascular Anomalies. The outcome was assessed with a clinical examination and a questionnaire. Results The lymphatic malformations were localised to the head/neck (60%), the trunk (20%) and the extremities (6%) or involved with more than one region (14%). Patients with microcystic (10%), macrocystic (21%) and mixed lymphatic malformations (69%) underwent a median number of three, two and two injection treatments, respectively. The median age at the first injection was 3.4 years. Good or excellent clinical outcomes were seen in 70% of the patients. The number of injections, previous treatment and lesion localisation, but not time to follow‐up and cyst size, predicted the clinical outcome. Conclusion OK‐432 treatment resulted in a successful outcome in 70% of patients with lymphatic malformations. The long‐term outcome was comparable to the short‐term outcome.